PENGARUH LUAS TEBANGAN HUTAN TANAMAN AKASIA TERHADAP KARAKTERISTIK HIDROGRAF BANJIR - Ning Indar Rukmi; Rasoel Hamidy; Mubarak Mubarak (Program Pascasarjana Universitas Riau, 2013)
One of the forest functions is the protection for water ecosystem along a watershed. Theactivities of extensive acacia logging area near the watershed of Sipatak by PT. SumateraSylva Lestari currently have not paid attention on the environmental condition, especiallythe hydrologic aspect. The present research sought to investigate the effect of the extensivelogging acacia on the flood hydrographic characteristic. The research was expected to comewith the proper acacia logging area. The land coverage and curve number analysis wereperformed using software program ArcView GIS 3.3 which was based on Table SCS CurveNumber. The average rain of the watershed was calculated using Polygon Thiessentechnique and the plan maximum daily rain was obtained from a frequency analysis towardthe average rain of the watershed. The hydrographic units was obtained from 10 floodincidences using Collins’ technique. The scenario of the forest logging pattern was madeaccording to the prevailing provision at PT. Sumatera Sylva Lestari. The floodhydrographic analysis was performed using Software HEC-HMS 2.2.2 by doing acalibration and verification to obtain the watershed parameter which would be used in theflood hydrographic simulation resulting from the logging. The initial value of the subwatershed of Sipatak was 78.558. The logging at sub watershed of Sipatak up to 79.496%resulted in the increase of CN to be 83.49. The increase of the CN resulted in the increaseof the peak debit up to 71.60% and the runoff volume was 71.04%. The trend line of peakdebit increase and the runoff volume resulting from the forest logging depended on thelogging forest area and the rain input. To avoid the over capacity of the watershed ofSipatak, the logging area should be 120.30 hectare or 32.69%.